Antineoplastic Agents. 590. The X-ray Crystal Structure of Dolastatin 16 and Syntheses of the Dolamethylleuine and Dolaphenvaline Units - Pettit, George R. (2011)
Three advances necessary to bringing dolastatin 16 (1) into full-scale preclinical development as an anticancer drug have been accomplished. The X-ray crystal structure of dolastatin 16 has been solved, which allowed stereoselective syntheses of its two new amino acid units, dolamethylleuine (Dml) and dolaphenvaline (Dpv), to be completed as summarized in reaction Schemes 1 and 3, respectively. The X-ray crystal structures of synthetic Z-Dml and TFA-Dpv have also been completed.